Rate of cesarean section among breech deliveries in Ethiopia: a systematic review and meta-analysis - Mussa, Ibsa; Debella, Adera; Regassa, Lemma Demissie; Ahamed, Badhasa; Jibro, Usmael; Eyeberu, Addis (Frontiers in Surgery, 2025)
BackgroundBreech deliveries are a significant public health concern in developing countries. The World Health Organization (WHO) declared that the cesarean section rate should not be higher than 10%–15%. As unnecessary C-sections may be associated with an increased risk of maternal and neonatal mortality, this meta-analysis was aimed at determining the rate of caesarean sections among breech deliveries in Ethiopia.MethodsAll published and unpublished articles were obtained from legitimate databases and websites. The PRISMA guidelines were used to conduct this systematic review and meta-analysis. The meta-analysis of the primary and secondary outcomes was performed using STATA version 18. The overall effect size with a 95% CI was estimated using the random effect model with the Der Simonian Liard method. A sensitivity analysis using a leave-one-out meta-analysis was computed.ResultsThis meta-analysis included a total of 57,236 mothers who had breech deliveries. The pooled prevalence of breech deliveries among women in Ethiopia was 5% [95% CI: 4, 6]. The overall pooled cesarean section rate among breech deliveries in Ethiopia was 41% (95% CI: 29–54).ConclusionsIn this review, the pooled prevalence of breech deliveries among women in Ethiopia was 5%, and the overall rate of caesarian section among the breech deliveries was 41%. This finding pointed out that two out of every five pregnant women with breech presentation gave birth by cesarean section in Ethiopia. Therefore, the finding implies that both the government and all the concerned stakeholders shall be given particular emphasis made on strengthening antenatal care services and ensure more women have access to skilled healthcare professionals during childbirth. This can help in providing appropriate interventions, support to women and reducing the need for emergency and unnecessary breech deliveries. The result of this research are a baseline data for future researchers to conduct further studies to better understand the reasons behind the high rates and identify potential interventions and solutions specific to the African context.